Study About Burnout for International Islamic Education Students 2022 - Faatin, Annisa Nabilah; Nurfitria, Annisa (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to evaluate the factors causing academic burnout among students of the International Islamic Education program, class of 2022, semester 5. The focus of this research is to explore students' experiences and perceptions related to the academic burnout they have encountered, as well as the strategies they use to cope with it. This study employs a qualitative approach with a phenomenological method and thematic analysis. Data were collected through open-ended questionnaires distributed digitally to students who met the criteria. The findings show that excessive workload, emotional pressure, and multitasking between studies, organizations, and work are the primary factors contributing to academic burnout. Students experience difficulty in managing time and dealing with multiple tasks with overlapping deadlines. Additionally, the anxiety about task completion and pressure from various aspects worsen the burnout condition. This study provides valuable insights into the factors contributing to academic burnout and the need for a more holistic approach in supporting students' academic and mental well-being